Implementasi Media “Carika” Berbasis Model PBL Upaya Peningkatan Hasil Belajar Bahasa Indonesia pada Peserta Didik Kelas IV - Alya Putri Maradika Ningrum; Panca Dewi Purwati (CV. KAMPUS AKADEMIK PUBLISING, 2024)
The problem of learning difficulties of grade IV students of SD Negeri Kandangan 04, Semarang Regency is in the subject Indonesian the procedure text material, causing the learning outcomes of some students to have not reached completion. The purpose of this study is to describe the implementation of the media